Manganese alleviates heat stress of primary cultured chick embryonic myocardial cells via enhancing manganese superoxide dismutase expression and attenuating heat shock response. (February 2023) - Qin, Shizhen; Huang, Liang; Lu, Lin; Zhang, Liyang; Guo, Yanli; Xi, Lin; Liao, Xiudong; Luo, Xugang
Abstract: Manganese (Mn) is an essential trace element that has been shown to attenuate the adverse effects of heat stress in the heart of broiler breeders and embryos. However, the underlying molecular mechanisms involving this process remain unclear. Therefore, two experiments were conducted to investigate the possible protective mechanisms of Mn on primary cultured chick embryonic myocardial cells exposed to heat challenge. In experiment 1, the myocardial cells were exposed to 40 °C (normal temperature, NT) and 44 °C (high temperature, HT) for 1, 2, 4, 6 or 8 h. In experiment 2, the myocardial cells were preincubated with no Mn supplementation (CON), 1 mmol/L of Mn as the inorganic MnCl2 (iMn) or organic Mn proteinate (oMn) under NT for 48 h, and then continuously incubated under NT or HT for another 2 or 4 h. The results from experiment 1 showed that the myocardial cells incubated for 2 or 4 h had the highest ( P < 0.0001) heat-shock protein 70 ( HSP70 ) or HSP9 0 mRNA levels than those incubated for other incubation times under HT. In experiment 2, HT increased ( P < 0.05) the heat-shock factor 1 ( HSF1 ) and HSF2 mRNA levels as well as Mn superoxide dismutase (MnSOD) activity of myocardial cells compared with NT. Furthermore, supplemental iMn and oMn increased ( P < 0.02) HSF2 mRNA level and MnSOD activity of myocardial cells compared with the CON. Under HT, the HSP70 and HSP9 0 mRNA levels were lower ( P < 0.03) in iMn group than in the CON group, in oMn group than in iMn group; and the MnSOD mRNA and protein levels were higher ( P < 0.05) in oMn group than in the CON and iMn groups. These results from the present study indicate that supplemental Mn, especially oMn, could enhance the MnSOD expression and attenuate heat shock response to protect against heat challenge in primary cultured chick embryonic myocardial cells. Highlights: Heat stress increases heat-shock protein/factor expression in chick myocardial cells. Manganese increases manganese superoxide dismutase expression. Organic manganese proteinate alleviates heat shock response.